Perl Hacks: Tips & Tools for Programming, Debugging, and Surviving - Chromatic (ShroffPublising /O'Reilly, 2006)
A guide to getting the most out of Perl covers such topics as productivity hacks, user interaction, data munging, working with modules, object hacks, and debugging.